(untitled) (Papeles, 2011)
This paper proposes the development of certain skills in training teachers in the use of information and communication technology (ICT). In today’s educational settings, the use of computer-based environments are becoming more common in the learning process of students and it involves the active participation of teachers in the design and development of computational scenarios that are flexible preferences learning and subjects that suit their individual differences. To this extent, these scenarios could be used by students effectively and thus achieve desired learning goals. This proposal is based on the developments being conducted by the research group Cognitek National Pedagogical University.